All lignin-based sponge encapsulated phase change composites with enhanced solar-thermal conversion capability and satisfactory shape stability for thermal energy storage. (October 2022) - Shen, Rongbiao; Lian, Peng; Cao, Yan; Chen, Ying; Zhang, Li; Sheng, Xinxin
Abstract: To promote the high-value utilization of lignin, a novel, all lignin-based chemically crosslinked sponge (CCL) was prepared and used to encapsulate phase change materials (PCMs) to solve problems associated with PCM leakage in practical application. In a straightforward, one step vacuum impregnation method, myristyl alcohol (MA), n-docosane (C22), and polyethylene glycol (PEG) phase change materials were encapsulated in the CCL sponges that were used as supporting material to prepare CCLPCMs, which were named as MA/CCL, C22/CCL, and PEG/CCL, respectively. Benefiting from the strong capillary action provided by the unique 3D continuous porous structure of the CCL, the mass loading of PCMs in the corresponding CCLPCMs are reached up to 93.1 ± 1.5 %, 90.2 ± 1.2 %, and 91.2 ± 0.6 %, respectively. It is also worth noting that η values of the corresponding CCLPCMs reached 99.4 ± 0.9 %, 100.9 ± 1.0 %, and 99.7 ± 1.0 %. The CCLPCMs showed excellent encapsulation capabilities, thermal reliability after 300 heating and cooling cycles and high solar-to-heat conversion capability over 30 cycles. These results provide a fresh, green, sustainable, and promising strategy to promote high-value utilization of lignin and design shape stability PCMs for heat energy storage. Graphical abstract: Unlabelled Image Highlights: All lignin-based sponge is prepared by chemical cross-linking followed by freeze-drying process. Well-defined 3D porous structure provides an ideal encapsulation for MA, C22, and PEG. High PCM loading rates of MA/CCL, C22/CCL, and PEG/CCL are 93.1±1.5%, 90.2±1.2%, and 91.2±0.6%, respectively. CCLPCMs exhibit excellent thermal reliability after 300 heating and cooling cycles.